Capture of UAVs through GPS spoofing using low-cost SDR platforms - Gaspar, J. (2020)
The increased use of unmanned aerial vehicles (UAVs), better known as drones, by civilians has grown exponentially and their autonomous flight control systems have improved significantly, which has resulted in a greater number of accidents and dangerous situations. To help resolve this problem, in this paper, we address the use of low-cost Software Defined Radio (SDR) platforms for simulating a global navigation satellite system (GNSS), more specifically the global positioning system (GPS), in order to transmit false signals and induce a location error on the targeted GPS receiver. Using this approach, a defensive system can be implemented which can divert, or even take control of unauthorized UAVs whose flight path depends on the information obtained by the GPS system.